Metabolic Costs During Backward Running with Body Weight Support - Masumoto, Kenji; Galor, Kendell; Craig-Jones, Andrew; Mercer, John A. (International Journal of Sports Medicine, 2019)
We investigated metabolic costs, rating of perceived exertion (RPE), stride frequency (SF), and preferred speed (PS) during forward and backward running at different levels of body weight support (BWS). Participants completed forward and backward running on a lower body positive pressure treadmill at their preferred speed for forward and backward running at 0%BWS, 20%BWS, and 50%BWS. Oxygen uptake (V̇O2), heart rate (HR), RPE, SF, and PS were measured. HR, RPE, and SF during forward and backward running decreased with increasing BWS (P<0.05).V̇O2 during both forward and backward running at 50%BWS was significantly lower than when running at 0%BWS (P<0.01). However, PS during forward and backward running increased with increasing BWS (P<0.01). Furthermore,V̇O2 was different between running directions only when running at 0%BWS (P<0.01). HR and RPE were not different between running directions (P>0.05). SF during backward running was higher than that of forward running (P<0.01). PS during backward running was lower than when running forward (P<0.001). Our observations suggest that individuals may select PS and SF during running with BWS in a way that resulted in similar metabolic costs, regardless of direction of locomotion.
Keywords: running direction, body weight support; preferred gait patterns